Synchronous occurrence of anaplastic, follicular and papillary carcinomas with follicular adenoma in thyroid gland - Ganguly R; Mitra S; Datta A (Indian Journal of Pathology and Microbiology, 2010)
Various combinations of thyroid carcinomas have been reported including those between different cancers of follicular cell origin and those between follicular and C-cell histogenesis. Accordingly, anaplastic carcinomas have been seen to coincide with simultaneous papillary and follicular cancers. We report a case of composite anaplastic and papillary cancer on one thyroid lobe with a follicular carcinoma in the other lobe in a female patient aged 64 years. The patient also had a separate and independent follicular adenoma in the same lobe as the composite anaplastic and papillary carcinoma. The papillary carcinoma was continuous with the anaplastic carcinoma. The findings were supported by immunohistochemistry. The patient was managed by a total thyroidectomy with bilateral modified radical neck dissection followed by chemotherapy. However, she died two months after surgery. The common follicular cell origin will explain the concurrent presence of all these cancers. This could result from the dedifferentiation of a pre-existing differentiated carcinoma.